2016
DOI: 10.3892/mmr.2016.4981
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic acid prevents enteritis through reduction of NF-κB p65 and p38MAPK expression in rat

Abstract: Glycyrrhizic acid has a variety of biological properties, including a protective function in the liver, and anti‑inflammatory, anti‑ulcer, anti‑anaphylaxis, anti‑oxidant, immunoregulatory, antiviral and anticancer activities. The efficacy of glycyrrhizic acid can be increased when combined with other medicines. In the present study, the potential protective effects of glycyrrhizic acid against enteritis in rats, and its role in regulating anti‑inflammation, anti‑oxidation, angiogenic and apoptotic mechanisms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…e total polyphenolic ingredients were shown as milligrams of gallic acid equivalent per 100 grams of MOLE. e standard curve used was gallic acid at different concentrations (25,50,100,150, and 200 μg/ml) to prepare the standard curve. For each standard concentration and sample, the absorbance at 760 nm was measured, and the calibration curve was obtained and calibrated.…”
Section: Total Polyphenolic Compound Estimation Chemical Composition and Ultraviolet-visible (Uv-vis) Spectroscopy Of Molementioning
confidence: 99%
“…e total polyphenolic ingredients were shown as milligrams of gallic acid equivalent per 100 grams of MOLE. e standard curve used was gallic acid at different concentrations (25,50,100,150, and 200 μg/ml) to prepare the standard curve. For each standard concentration and sample, the absorbance at 760 nm was measured, and the calibration curve was obtained and calibrated.…”
Section: Total Polyphenolic Compound Estimation Chemical Composition and Ultraviolet-visible (Uv-vis) Spectroscopy Of Molementioning
confidence: 99%
“…1a and 1b), which included nineteen flavonoids, three organic acids, three monoterpenoids, two triterpenoid saponins, two alkaloids, and two other types of compounds. The contents of seven components with antiviral, antimicrobial, and anti-inflammatory activities [10][11][12][13][14][26][27] in GGD were determined by high-performance liquid chromatography (HPLC) as 0.63 mgg -1 gallic acid, 21.46 mgg -1 puerarin, 3.74 mgg -1 paeoniflorin, 3.08 mgg -1 daidzin, 0.48 mgg -1 daidzein, 0.24 mgg -1 cinnamic acid, and 1.8 mgg -1 glycyrrhizic acid (Fig. 1c).…”
Section: Characterization Of Chemical Constituents In Ggdmentioning
confidence: 99%
“…GGD treatment significantly reduced the virus titers in lung tissue and alleviated pathological damage in mice infected with H1N1 (0.8 LD 50 ). Some components in GGD have immunomodulatory and anti-inflammatory activities [10][11][12][13][14][15] . Thus, further studies are required to verify the anti-inflammatory and immunomodulatory hypothesis of GGD in the treatment of influenza.…”
Section: Ggd Reduced Virus Titers In Lung Tissue and Alleviated Iavinmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] Previous studies have shown that GA can regulate several important signaling proteins, including those that belong to cysteine-dependent aspartate-specific protease (caspase) and the Bcl-2 families, the nuclear factor-kappaB (NF-κB) protein, the high mobility group box-1 (HMGB1) protein, the extracellular regulated protein kinases (ERK), the phosphatidylinositol 3-kinase (PI3K)/AKT kinases and the c-Jun N-terminal kinase (JNK). [19][20][21][22] However, a limited number of reports have investigated mechanism by which GA affects GC.…”
Section: Introductionmentioning
confidence: 99%